The architect's guide to effective self-presentation - Luescher, Andreas (London : Routledge, 2013)
'In today's increasingly competitive marketplace, the creation of a successful resume is a vital skill needed by architectural students and professionals alike. This book demystifies the architecture resume, its working strategy and its purposes. The book guides readers through the process of thinking through, prioritizing, characterizing and expressing career profiles in written and visual form. Readers will learn about presentation and the evolving vehicles for showcasing that presentation. In addition, the timely and important issue of how to transform one type of presentation from a hard copy, to an on-screen review, to an interactive web-page is covered in detail. The book re-evaluates traditional concepts of resume making, seeking to define the resume as a detailed process of marketing one self. By doing so, the text provides a new and revised set of tools for thinking about the creation of an architecture resume. In tandem with the author's other book The Architect's Portfolio or on its own, this book is essential reading for anyone looking to further their architectural career'--
Includes index.
Includes bibliographical references and index.
Keywords: Architects -- Vocational guidance; Architecture -- Vocational guidance